A low-profile ±45º dual-polarized antenna based on metasurface and its arrays for base station applications. Issue 14 (22nd September 2018) - Ta, Son Xuat; Nguyen, Minh Duc; Nguyen, Thi Hai-Yen; Nguyen, Truong Khang; Nguyen, Khac Kiem; Dao-Ngoc, Chien
Abstract: This paper presents a low-cost, low-profile, ±45º dual-polarized antenna based on metasurface for base station applications. The antenna consists of two ±45º printed dipoles, which are fed by novel printed baluns for allowing broad operational bandwidth and a high port-to-port isolation. The antenna is backed by a metallic cavity reflector to obtain the broadside radiation. The metasurface, which is a periodic lattice of square patches printed on a thin low-cost substrate, is inserted between the radiator and the reflector to achieve the low-profile. The single element with an overall size of 160 mm × 160 mm × 16 mm (0.96λo × 0.96λo × 0.096λo at 1.8 GHz) yields a voltage standing wave ratio (VSWR) < 2 bandwidth of >29% for both ports, an isolation of >34 dB, a gain of >8.4, and a radiation efficiency of >80%. Also, a four-element array based on the proposed antenna is fed by non-uniform feeding networks to achieve a low sidelobe level (SLL). The array yielded an isolation of > 20 dB, a gain of >11.7 dBi, and an SLL of <–20 dB for both ± 45º polarizations.